MILLENNIAL TRUST THROUGH ENDORSER CREDIBILITY ON LOCAL INFLUENCER ENDORSEMENT ON INSTAGRAM - Karouw, Deatara E. Z.; Worang, Frederik G.; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2019)
Abstract: Endorsement as a marketing strategy using local influencer instead of celebrity in North Sulawesi is being used by many SMEâ€™s nowadays. This study aims to find outÂ how is the millennial trust through endorser credibility on local influencer endorsement on instagram. In this study endorser credibility is derived from 3 factors which are expertise, attractiveness and trustworthiness. This research is a qualitative research and uses in-depth interview. This research sampling size are 15 respondents and are taken from people aged 23-39, who are instagram users and have seen endorsement activity of local influencer on instagram. The result of this research is expertise rated as a more important indicator in endorser credibility over attractiveness, however local influencers are perceived as no experienced endorser. Result also shows physical appearance and familiarity are the two more important dimensions in attractiveness over likeable and similar. From the results, it is recommended for brand who is doing endorsement activity using local influencer to have the priority of finding endorser who has the expertise especially experience rather than attractive look and endorser who is interactive, constantly updating and enjoy making connection with viewers that make them more familiar.Â Keyword: endorsement, endorser credibility